Studies of some volatile compounds of main group elements - Aldridge, S; Aldridge, Simon (1996)
﻿ Methylzinc tetrahydroborate, [MeZnBH4], has been prepared by two routes and the structure of the solid determined by X-ray crystallography to reveal helical polymers in which MeZn and BH4 units alternate. The latter functions as a bidentate ligand with respect to each of the adjacent metal atoms. Investigation by mass spectrometry and matrix isolation shows that the vapour consists of an equilibrium mixture of monomeric and dimeric species. The pattern of infrared bands for the monomer is characteristic of a bidentate BH4 group, a finding consistent with the results of DFT calculations. Disproportionation into [Me2Zn] and [Zn(BH4)2] is a common feature of the chemistry of methylzinc tetrahydroborate, although it has been possible to isolate and characterize the adduct [MeZnBH4.SMe2]. The reaction between [B4H10 and [Me2Zn] in the gas phase affords colourless acicular crystals of [(MeZn)2B3H7] in yields of ca. 10%. This compound has been characterized by chemical analysis and by NMR and vibrational spectroscopy. X-ray crystallography reveals that the product is a dimer, [(MeZn)2B3H7]2, featuring two distinct zinc environments. Two B3H7ZnNe ligands, formally derived from B3H8 by replacement of a µ2-H by a µ2-ZnMe unit, each function in a bis(bidentate) manner linking together two other MeZn centres through pairs of Zn-H-B bridges. The structures of several aluminium tetrahydroborates in the solid phase have been investigated by X-ray diffraction. The structure of dimethylaluminum tetrahydroborate has been shown to consist of helical polymeric chains in which Me2-Al and BH4 units alternate. Here, too, the BH4 groups exhibit bidentate ligation with respect to each of the adjacent metal atoms, although the degree of interaction between the metal centre and the BH4 group is somewhat less than in [MeZnBH4 ]. Solid aluminium tris(tetrahydroborate) exhibits two phases with a transition temperature in the range 180-195 K. Each phase is made up of discrete Al(BH 4 )3 units, the principal differences relating to the packing of the individual molecules. In the a phase the Al(BH 4 )3 molecules display an angle of 78.2° between the AlB3 and Al(µ-H)2 planes and are disposed about a 21 crystallographic screw axis; in the ß phase the molecular units conform to D3h symmetry. Dimethylindium octahydrotriborate, [Me2 lnB3 H8 ], has been synthesized by the reaction between trimethylindium and tetraborane(10) and characterized by chemical analysis and by NMR and vibrational spectroscopy. X-ray diffraction of a single crystal reveals that the solid consists of [Me2 lnB3 H8] units, although there is evidence of charge separation in the sense [Me2ln]+[B3 H8 ]- and of secondary interaction between terminal hydrogen atoms and adjacent indium centres. The infrared spectrum of the matrix-isolated vapour is consistent with a monomeric structure similar to that of [Me2 AlB3 H8].